Incidence of agroecological-based practices in urban vegetable gardens: effect on crop diversity and production levels - De Paz, Manuel; Nabaes Jodar, Diego; Ocariz, María Paula; Mantiñan, Camila; Raffo, Fernando; Garibaldi, Lucas Alejandro (Taylor and Francis, 2025)
Agroecological-based practices (ABPs) play a vital role in urban vegetable gardens, enhancing the quality of life. However, factors driving ABP implementation and their impact on crop production and diversity are not fully understood. Our study assessed the influence of socio-economic and environmental characteristics on ABP adoption, crop diversity, and total weight vegetable production in San Carlos de Bariloche, Argentina. Through interviews and a multi-model inference approach, we found that ABP implementation is tied to gardener experience and formative assets (e.g. horticultural experience, specific training). Crop diversity, integral to ABP, is affected by farming practices and farmer characteristics (Farm animals, Pollinator-friendly practices, Experience, Additional training and Environmental knowledge). The Total weight produced was primarily influenced by the type of garden, the gardener’s experience and some ABPs. Long-standing commercial and community objectives and the use of farm animals and commercial seed led to greater production. Strengthening key drivers, such as farmer training, through public policies (e.g. income generation, financing, specific training, land access) can bolster the role of urban gardens in providing a healthy environment and promoting food sovereignty.